Stranding of larval nase (Chondrostoma nasus L.) depending on bank slope, down-ramping rate and daytime - Führer, Simon; Hayes, Daniel S.; Hasler, Thomas; Graf, David R. M.; Fauchery, Elora; Mameri, Daniel; Schmutz, Stefan; Auer, Stefan (Frontiers in Environmental Science, 2022)
Rapid water level decreases due to hydropeaking are known to negatively affect riverine biota, mainly due to the stranding of organisms in the river bank area that becomes regularly dewatered. Even though studies of the last decades have focused on salmonid fish, also cyprinids may be affected. However, limited knowledge is available of this fish family. Therefore, we conducted mesocosm experiments under semi-natural conditions, simulating single hydropeaking events at two different lateral bank slopes (2% and 5%) with varying down-ramping rates (0.7–3.0 cm.min 1) during day and night. As a response parameter, we quantified stranding rates of different larval stages (III-IV and V) of common nase (Chondrostoma nasus L.) from different larvae developmental stages. The experiments revealed that lower sloped banks exhibited distinctly higher stranding rates than steeper ones. Daytime revealed a similar pattern, with more fish becoming stranded at night than during the day, and this was consistent for all down-ramping rates. The data also indicate increased stranding with higher down-ramping rates, particularly at low sloped riverbanks, and interaction effects between the tested parameters. Overall, this study, for the first time, quantifies the consequences of flow down-ramping on nase larvae, also revealing differences between early life cycle stages. The gained information will, therefore, advance the ongoing discussion on hydropeaking mitigation by providing a deeper understanding of the effects of artificial sub-daily flow fluctuations on the early life stages of cyprinid fish. Our results can inform management and policy to sharpen existing mitigation concepts and fine-tune hydropower operations to reduce negative effects on riverine ecosystems.